PENDAMPINGAN PEER GROUP UNTUK MENURUNKAN RESIKO TRIAD KRR DI SMAN 2 SIAK HULU - Yeyen Gumayesty; Raviola; Hastuti Marlina (Jurnal Pengabdian UntukMu NegeRI, 2019)
Abstract Three main problems of adolescents in the field of reproductive health or known as the Adolescent Reproductive Health Triad are sexuality, drugs, HIV / AIDS increased, it has an impact on the quality of adolescent reproductive health as the next generation of the nation. Various research results on this matter are known that all individuals, especially adolescents are at risk of experiencing the Adolescent Reproductive Health triad because of the influence of friendship. To overcome this problem, collaboration between health institutions and schools is needed, in this case 2 Siak Hulu High School. The community service activities went smoothly and succeeded in improving the cognitive, affective and psychomotor aspects of the participants. In the affective aspect, it also increased from before getting mentoring on TRIAD KRR with an average of 41 and increased after participating in mentoring with an average of 75.5. In the psychomotor aspect, which was considered more on the Agent Genre aspect in the skills to spread information about the TRIAD KRR to peers with a mean difference before and after mentoring of 33.4, meaning participants were more skilled at educating peers after getting mentoring. Key words: Peer Group, Genre Agent, TRIAD KRR Abstrak Tiga masalah utama remaja dalam bidang kesehatan reproduksi atau dikenal dengan Triad KRR yaitu seksualitas, napza, HIV/AIDS meningkat, hal tersebut berdampak terhadap kualitas kesehatan reproduksi remaja sebagai generasi penerus bangsa. Hasil penelitian mengenai hal tersebut diketahui bahwa semua individu khususnya usia remaja berisiko mengalami triad KRR karena pengaruh pertemanan. Untuk mengatasi masalah tersebut diperlukan kerjasama antara institusi kesehatan dengan pihak sekolah, dalam hal ini SMA 2 Siak Hulu. Kegiatan pengabdian ini berjalan dengan lancar dan berhasil meningkatkan aspek kognitif , afektif dan psikomotor peserta. Pada aspek kognitif nilai rata-rata pretest 43,5 dan meningkat setelah pendampingan dengan nilai rata-rata post tes 78. Pada aspek afektif ikut meningkat dari sebelum mendapatkan pendampingan mengenai TRIAD KRR dengan rata-rata 41 dan meningkat setelah mengikuti pendampingan dengan rata-rata 75,5. Pada aspek psikomotor yang dinilai lebih kepada aspek Agent Genre dalam keterampilan menyebarkan informasi mengenai TRIAD KRR kepada teman sebaya dengan selisih rerata sebelum dan setelah pendampingan sebesar 33,4, artinya peserta lebih terampil melakukan edukasi terhadap sebaya setelah mendapatkan pendampinganah Kata Kunci: Peer Group, Agen Genre, TRIAD KRR